2008
DOI: 10.1038/modpathol.3800993
|View full text |Cite
|
Sign up to set email alerts
|

Presence of simian virus 40 in diffuse large B-cell lymphomas in Tunisia correlates with germinal center B-cell immunophenotype, t(14;18) translocation, and P53 accumulation

Abstract: Previously we have reported the presence of simian virus 40 DNA in 56% of diffuse large B-cell lymphomas in Tunisia. Here, we investigated the relationship between the status of simian virus 40 and t(14;18) translocation, germinal center status, and P53 and BCL2 expression to assess the clinical and biological relevance of simian virus 40 presence in diffuse large B-cell lymphomas. Therefore, we evaluated by immunohistochemistry the expression patterns of CD10, BCL6, MUM1, BCL2, and P53 in 86 diffuse large B-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…This observation supports a role of SV40 in the inactivation of P53 in human BC. Similar results have been also demonstrated in human mesotheliomas, brain tumors, and lymphomas [60][61][62].…”
Section: Discussionsupporting
confidence: 84%
“…This observation supports a role of SV40 in the inactivation of P53 in human BC. Similar results have been also demonstrated in human mesotheliomas, brain tumors, and lymphomas [60][61][62].…”
Section: Discussionsupporting
confidence: 84%
“…For the remaining 42 cases (9 GCB and 33 ABC), we again used the data-sort function and found that sequential use of either monoclonal or polyclonal BCL6 (≥30%) followed by FOXP1 (≥80%) classified 37 (88%) of the cases correctly. Monoclonal BCL6 was chosen because it does not require additional procedures to decrease background staining, and it was the BCL6 antibody most commonly used in recent studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)23). Whereas changing the cutoffs of monoclonal BCL6 or FOXP1 in this algorithm led to worse overall accuracy, we found that changing the cutoffs for GCET1 and MUM1 to ≥80%, and CD10 to ≥30%, did not affect the concordance with the GEP classification.…”
Section: Translational Relevancementioning
confidence: 75%
“…To facilitate translational application of the GEP classification for prognostication using formalin-fixed, paraffinembedded tissues, we have previously proposed an immunohistochemical (IHC) stain algorithm (Hans' algorithm) using three antibodies [CD10, multiple myeloma oncogene 1 (MUM1), and polyclonal B-cell lymphoma 6 (BCL6)] to classify DLBCL into GCB and non-GCB (ABC and unclassified) subtypes (9). It resulted in a concordance of ∼80% when compared with the GEP classification (9), and subsequent studies have yielded conflicting results regarding its prognostic prediction (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most of these studies included patients from the pre-rituximab era (10)(11)(12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23), but the controversy has extended to R-CHOP-treated patients as well (15,19,22,23).…”
mentioning
confidence: 99%
“…A recent report reflects on the common mechanism of transformation by small DNA viruses, such as SV40, and the inactivation of p53 (69). Except for one report, correlating SV40 and p53 in diffuse large B-cell lymphoma in Tunesia (70), such a correlation has not been studied as far as we know for childhood lymphoproliferative disorders. That study looked for the accumulation of p53 in the nucleus, not for p53 mutations, specifically.…”
Section: Introductionmentioning
confidence: 96%